Quality of cowpea seeds: A food security strategy in the tropical environment - de Aguila Moreno, Leticia [UNESP]; de Oliveira, Gustavo Roberto Fonseca [UNESP]; Batista, Thiago Barbosa [UNESP]; Bossolani, João William [UNESP]; Ducatti, Karina Renostro [UNESP]; Guimarães, Cristiane Carvalho [UNESP]; da Silva, Edvaldo Aparecido Amaral [UNESP] (Public Library of Science (PLoS), 2022)
What is the relation between seed quality and food security? Here we built a summary diagram that links the development stages of the seeds with their potential of providing grain yield. This idea was tested using cowpea as a model crop, grown in a tropical environment. Initially, seed quality attributes such as water content, dry weight, germination, vigor, and longevity were characterized during seed development. With this, we were able to elucidate at which point the late maturation phase and the acquisition of seed with superior physiological quality starts. From these data, the proposed summary diagram highlighted the seed quality as a technological basis for generating a more productive plant community. It also showed that only seeds with a high-quality profile have a better chance to establishment in an increasingly challenging agricultural environment. Overall, we bring the concept that cowpea seeds with superior quality besides being the essential input for tropical agriculture is also a strategy that can contribute food security.